Slow Tourism Possibilities in Cimande Tourism Village – West Java - Sari, Dhanik Puspita (E-Journal of Tourism; Volume 9 Number 1 (March 2022)DO - 10.24922/eot.v9i1.82895, 2022)
Cimande Tourism Village is a village located in Tarikolot, Bogor Regency, Indonesia. It has a lot of tourism potential, both natural tourism, cultural tourism, and artificial tourism. This green, calm and cultural area is expected to be able to provide alternative types of tourism that are thick with experience and also have a significant economic impact by extending the length of stay of tourists. The purpose of this research is to see how much potential Cimande Tourism Village has to be applied as slow tourism. Slow tourism is a form of tourism theme which stresses quality in gaining experience during tourism activities rather than quantity. The study used descriptive qualitative methods. A checklist is given to tourism academics whose results are recapitulated and then analyzed and described clearly. The results found that most of the key elements of slow tourism could be found and it could also be applied in order to establish the form of slow tourism as alternative tourism. This research only focuses on the supply side from an academic perspective. Slow tourism is not a common form of tourism, in Indonesia, no research has ever been conducted on slow tourism before, and this paper is expected to be an early opening door in tourism research in Indonesia, especially in them of slow tourism. Keywords: Slow Tourism, alternative tourism, tourism village